(untitled) (Scientific journal of the Fergana State University, 2023)
In this article on the basis of research methods of field expeditions, geographical information systems, analysis of bibliographic literature cone-shaped plain landscape complexes with unique natural conditions in Middle Zaravshan are analyzed in terms of their natural conditions, occurrence, formation and their use in the economy. As a result, the cone-shaped reversal allowed to evaluate the landscape complexes in terms of their utilization in the sectors of the economy.